THE EFFECT OF BIDARA FRUIT EXTRACT (Ziziphus Mauritiana.) AND IMMERATION TIME ON THE PHYSICAL AND ORGANOLEPTIC QUALITY OF CHICKEN BREAST MEAT BROILER - A. A. A. F., Sumadi; Okarini, I. A.; Wijana, I W. (Jurnal Peternakan Tropika, 2021)
This research aims to determine concentration of bidara fruit ( Ziziphus Mauritiana .) in soaking the meat and its effect on the characteristics of broiler meat. The research was conducted in October 2020 - November 2020 at the Laboratory of Animal Product Technology and Microbiology, Faculty of Animal Husbandry, Udayana University. This study used a completely randomized design (CRD) with a factorial pattern with the first factor being the concentration of bidara fruit extract and the second factor of soaking time. The concentrations of bidara fruit extract are Eb1 5% and Eb2 25% and the soaking time is 0 minutes, 30 minutes, and 60 minutes. The variables observed were cooking losses, pH value, total yield, aroma and taste. The results showed that there was no significant difference in the both factor  interaction on the cooking losses, total yield, aroma and taste (P> 0.05) and in the concentration factor of bidara fruit extract, when there was a significant difference (P <0.05) in the factor at the time of marination. There was a significant difference in the pH value (P <0.05) at factor of concentration of bidara fruit extract and factor of marination time, but no significant difference in the both factor interaction. The conclusion based on the results of the analysis above shows that there is no interaction between the two treatment factors. In the extract concentration factor, a decrease in the pH value of the meat was obtained. In the treatment factor, the duration of marination affects the physical properties (decrease in cooking losses and pH, increase in total yield) and organoleptic (increase in taste and aroma preferences) of meat. Key words : marination, chicken breast, bidara fruit